Iron status in children with acute COVID-19 and paediatric inflammatory multisystem syndrome during infection and after recovery - Mai S. El-Meshad; Angi Adel Alwakeel; Reham M. El-Farahaty; Hyam Sameh Nada; Mayada S. Zeid (SpringerOpen, 2024)
Abstract Background COVID-19 has significant effects on organ function, particularly on lung function and iron metabolism. Studies have shown increased levels of ferritin, an iron storage protein, in COVID-19 patients, indicating potential changes in iron utilization. Research has focused primarily on adults, with limited studies on paediatric patients and a lack of comparisons with MIS-C patients. This study aimed to assess iron status in paediatric COVID-19 patients using traditional and new biomarkers, soluble transferrin receptors (sTfR) and Reticulocyte hemoglobin equivalent (RET-He), to improve diagnosis and prognosis. Additionally, we sought to compare iron status between acute COVID-19 patients and MIS-C patients and evaluate the relationships among iron dysmetabolism, disease severity, and prognosis in paediatric patients. The study also involved monitoring iron status during and after infection to understand its impact on patient severity and prognosis. Methods A cohort study involving 49 patients aged 1 month to 18 years was conducted at the isolation department of Mansoura University Children's Hospital. The study included 36 patients with acute COVID-19 and 13 with multisystem inflammatory syndrome of childhood (MIS-C). Diagnosis was based on PCR from a deep nasopharyngeal swab or a positive antibody test. Follow-up of survivors was conducted 3 months after recovery. Blood samples were obtained during infection and at follow-up for CBC, Ret-He, iron kinetics, and sTfR analyses. Results Significant iron deficiency anaemia was observed in all patients during infection, with improvement after 3 months of recovery in survivors. The improvement was more obvious in MIS-C patients, with Hb and iron kinetics not significantly affected by disease severity. The STfR was significantly lower in nonsurvivors than in survivors. The ROC curve showed that a baseline sTfR ≤ 18 nmol/L was a statistically significant difference between nonsurvivors and survivors (area under the curve (AUC) = 0.810, p < .001), with 66.7% sensitivity and 82.5% specificity. Regression analysis revealed that patients with baseline sTfRs ≤ 18 nmol/L were 5.9 times more susceptible to death. Conclusion This study revealed that COVID-19 in children caused iron deficiency anaemia, which improved within 3 months after recovery. Haemoglobin and sTfRs were identified as reliable indicators of IDA in these patients, unlike iron kinetics and RET-He.